Recycled Paper Mill Sludge With Sulphur Oxidizing Bacteria As Biofilter To Treat Malodour From Palm Oil Mill Effluent - Kamarzaman, Fatin Farhana (2021)
One of the most problematic contaminants in biogas is the presence of hydrogen sulphide (H2S) and ammonia (NH3), which are emitted from industrial processes and cause odour nuisance to the surrounding community. An investigation using recycled paper mill sludge (RPMS) as a new potential media in biofiltration process was carried out to study the characteristics and determine its suitability as a new media with its effect on the removal efficiency of H2S, NH3 and odour strength from palm oil mill effluent (POME). Numerous studies have proved that sulphur oxidizing bacteria (SOB) can help to enhance the removal of H2S concentration. Hence, in this study the bacteria of Paracoccus Solventivorans ATCC 700252 were used as SOB based on RPMS media by immobilization process. Based on final result, RPMS with immobilized SOB demonstrated reduction of H2S with higher removal efficiency of 64.02% with sulphate concentration is 21 mg/l compared to raw RPMS (46.84%). However, the removal efficiency of NH3 on raw RPMS is higher (49.64%) than RPMS with immobilized SOB (32.75%). For odour strength, the removal efficiency is higher occurs at RPMS media contained immobilized SOB (72.15%) than raw RPMS (66.89%) during 28 days. SOB has the ability to absorb the odorous ‘rotten egg’ smell and changes into elemental sulphur that is no longer hazardous. In this regard, the utilization of RPMS mixed with Paracoccus solventivorans ATCC 700252 (SOB) can create a new industry for application in H2S and odour removal, thus can protect the environment from odour pollution.